Comparative Study of Gleason 7 (3+4) and (4+3) Prostatic Adenocarcinomas with Prognostic Criteria and Immunohistochemical Profiles of AMACR, PSA and Ki-67 - Clarice F. E. M. Osório; Waldemar S. Costa; Carla B. M. Gallo; Luciano A. Favorito; Francisco J. B. Sampaio (International Brazilian Journal of Urology)
ABSTRACT Background: To compare Gleason 7 (3+4) and (4+3) prostatic adenocarcinoma (PC) with different prognostic criteria through immunohistochemical analysis with anti-PSA, anti-Ki 67 and anti-AMARC antibodies. Methods: We analyzed 221 surgical specimens from patients between 40 and 86 years-old (mean=63) with PC. The immunohistochemical study was performed with anti-PSA, anti-Ki 67 and anti-AMARC. The microscopic fields were photographed with an Olympus DP70 digital camera coupled to an Olympus BX51 microscope and archived in TIFF. Proportion and intensity criteria were used to quantify the anti-PSA antibody and for the anti-Ki 67 antibody, the quantification by similarity of this antibody in breast carcinomas. Anti-AMACR protein expression was based on four scores: negative, weak, moderate and strong. The statistical analysis was performed with the Graph Pad Prism 5 program. Results: In the Gleason score 7 (3+4) we had 91.72% in pT2 and 8.27% in the pT3 group; 8.27% recurrences, of which 90.90% in the pT2 group. In the Gleason score 7 (4+3) we had 77.27% in the pT2 group and 22.72% in the pT3 group and 10.22% of relapses, of which 66.66% in the pT2 group and 33.33% in the pT3 group. In 6.81% of cases there was an increase in the anti-Ki 67 index and in 2.27% of the cases, there was an increase in the immunoexpression of anti-p53 when comparing Gleason score 7 (3+4) with Gleason score 7 (4+3). Conclusion: Our study confirmed differences in the Gleason score 7 (3+4) and Gleason score 7 (4+3) of PC when comparing prognostic criteria. Anti-Ki 67 and anti-PSA antibody immunostaining showed a positive correlation as the Gleason score 7 increased from (3+4) to (4+3).